Gamified, Automated Virtual Reality Exposure Therapy for Fear of Spiders: A Single-Subject Trial Under Simulated Real-World Conditions - Lindner, Philip; Miloff, Alexander; Bergman, Camilla; Andersson, Gerhard; Hamilton, William; Carlbring, Per (Frontiers in Psychiatry, 2020)
Background: Virtual Reality exposure therapy (VRET) is an evidence-based treatment of phobias and recent research suggests that this applies also to self-contained, automated interventions requiring no therapist guidance. With the advent and growing adoption of consumer VR technology, automated VR intervention have the potential to close the considerable treatment gap for specific phobias through dissemination as consumer applications, self-help at clinics, or as blended treatment. There is however a lack of translational effectiveness studies on VRET treatment effects under real-world conditions. Methods: We conducted a single-arm (n=25), single-subject study of automated, gamified VRET for fear of spiders, under simulated real-world conditions. After setup and reading instructions, participants completed the automated, single-session treatment by themselves. Self-rated fear of spiders and quality of life served as outcome measures, measured twice before, and one and two weeks after treatment, and at a six-month follow-up. Session characteristics and user experience measures were collected at the end of the session. Results: Mixed-effects modeling revealed a significant and large (d=1.26) effect of treatment-onset on phobia symptoms (p<.001), and a small (d=0.49) effect on quality of life (p=.025). Results were maintained at a six-month follow-up (p>.053). The intervention was tolerable and practical. There were no significant correlations between any user experience measure and decrease in phobia symptoms (p>.209). Conclusions: An automated VRET intervention for fear of spiders showed equivalent effects on phobia symptoms under effectiveness conditions as previously reported under efficacy conditions. These results suggest that automated VRET applications are promising self-help treatments also when provided under real-world conditions. Pre-registration: Open Science Foundation, https://doi.org/10.17605/OSF.IO/78GUB